Service and infrastructure needs to support recovery programmes for Indigenous community mental health consumers. (27th December 2016) - Sayers, Jan M.; Cleary, Michelle; Hunt, Glenn E.; Burmeister, Oliver K.
Abstract: Mental health is a major concern in Indigenous communities, as Indigenous people experience poorer health outcomes generally, and poorer social and emotional well‐being throughout their lives, compared to non‐Indigenous populations. Interviews were conducted with 20 mental health workers from a housing assistance programme for Indigenous clients with mental illness. Service and infrastructure needs identified to support clients were classified under the following overarching theme 'supports along the road to recovery'. Subthemes were: (i) It is OK to seek help; (ii) linking in to the local community; (iii) trusting the workers; and (iv) help with goal setting and having activities that support their achievement. This paper highlights the importance of targeted housing and accommodation support programmes for Indigenous people to prevent homelessness, and the essential services and infrastructure required to support Indigenous clients' mental health needs. These insights may inform service review, workforce development, and further research.